2023
DOI: 10.22270/jddt.v13i1.5872
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antioxidant potential and phytochemical analysis of Terminalia mantaly and Terminalia ivorensis two plants of the Ivorian pharmacopoeia

Abstract: The neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease and amyotrophic lateral sclerosis are characterized by a significant increase in oxidative stress that can lead to cellular damage to neurons. In recent years, the antioxidant activity of medicinal plants has become important in research against cancer and neurodegenerative diseases. Terminalia mantaly and Terminalia ivorensis are two plants traditionally used to treat lesions, wounds, ulcers and hemorrhoids, malaria and yell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Besides its economic usage, TI also serves as a good source of phytochemicals for ethno-medicinal purposes [ 9 ]. In in vitro studies, TI has been reported to show antibacterial, antifungal, antioxidant and anti-plasmodial effects [ 10 – 13 ]. Whereas several in vivo studies have found TI to possess anti-inflammatory, anti-nociceptive, anti-psychotic, hepatoprotective and nephroprotective properties in mice and rats [ 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides its economic usage, TI also serves as a good source of phytochemicals for ethno-medicinal purposes [ 9 ]. In in vitro studies, TI has been reported to show antibacterial, antifungal, antioxidant and anti-plasmodial effects [ 10 – 13 ]. Whereas several in vivo studies have found TI to possess anti-inflammatory, anti-nociceptive, anti-psychotic, hepatoprotective and nephroprotective properties in mice and rats [ 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%